PENGARUH KUALITAS PELAYANAN DAN KINERJA KARYAWAN TERHADAP KEPUASAN KLIEN PADA KANTOR NOTARIS DAN PPAT PURWANTO, S.H., M.Kn DI KABUPATEN BREBES - Mardiana Nisa B; Suryani Ningsih; Nur Haliza Damayanti (Tamilis Synex: Multidimensional Collaboration, 2025)
Client satisfaction is very important for the sustainability and success of a business. The two main factors influencing client satisfaction are the quality of service and employee performance provided by the service provider. This research aims to determine the influence of service quality and employee performance on client satisfaction at Notary and PPAT offices Purwanto, S.H., M.Kn. This type of research is quantitative, using the Purposive Sampling Technique. The sample in the study was 70 respondents—data collection techniques through questionnaires. The data analysis techniques used are classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis tests. The results of the T-test show that service quality has a positive effect with a Tcount value (4.362>1.996) and a significant value of 0.000<0.05 on client satisfaction, employee performance has a positive and significant effect with a Tcount value (5.333>1.996) and a significant value of 0.000<0, 05 towards client satisfaction. The results of the simultaneous F test obtained Fcount 39,813> Ftable 3.13 with a significant value of 0.000<0.05. The research results show that service quality and employee performance partially or simultaneously significantly affect client satisfaction at the Brebes Regency's Purwanto, S.H., M.Kn Notary, and PPAT offices. There is a need to improve staff service when providing services to clients so that clients feel satisfied and can add more clients.